Analisis Determinan Tingkat Upah di Sumatera Barat - Lisa Febryanti; Dewi Zaini Putri (Universitas Negeri Padang, 2020)
This study aims to determine: (1) The effect of employment status on wage levels in West Sumatra. (2) The effect of education level on wage levels in West Sumatra. (3) Effect of gender on wage rates in West Sumatra. This type of research is descriptive and associative research. The type of data used in this study is the 2018 National Labor Force Survey (SAKERNAS) in West Sumatra Province sourced from the Central Statistics Agency (BPS) of West Sumatra Province. The method used in this study is the Logistic Regression Analysis Method. The results of the study show that: (1) Employment status with an unspecified time agreement has a significant positive effect on wage levels in West Sumatra, a certain time agreement has a positive and significant effect on wage levels in West Sumatra and an oral agreement has a negative and not significant effect on wage levels in West Sumatra. (2) The level of education has a positive and significant effect on wage levels in West Sumatra. (3) Sex has a positive and significant effect on wage rates in West Sumatra. From the results of this study, it is recommended to the Government of the Province of West Sumatra to set a Provincial Minimum Wage (UMP) according to a decent standard of living and provide strict sanctions to companies both private or government institutions that do not pay labor wages in accordance with the Minimum Wage Provibsi (UMP) in West Sumatra. This is done to improve the welfare of workers in the Province of West Sumatra.